Exploration of the homology among the muscles associated with the female genitalia of the three suborders of Psocodea (Insecta) - Cheng, Zixin (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2022)
By using μCT technology, we reconstructed 3D models of the female genital structures and associated muscles of seven species from three suborders of Psocodea (free-living species only, formerly known as independent insect order “Psocoptera”). The homology of the female genital structures and associated muscles of different species is discussed. A total of 21 muscle groups were observed, and except for one muscle, all were homologized throughout the order. Moreover, some of the homologous muscles could be identified confidently in holometabolan insects. Using the muscles as landmarks, we discuss the homology of the ovipositor valves between Psocodea and other neopteran insects. Most importantly, the ovipositor of the suborder Trogiomorpha was identified to consist of the well-developed external valve (V3) plus a remnant of the dorsal valve (V2). We also examined the phylogenetic information included in the female genital muscles and found that certain muscles provide useful information and support deeper nodes (e.g., monophyly of the suborder Psocomorpha). The present study of female genital muscles not only helps us to better understand the phylogeny of Psocodea but also provides a solid foundation for research on muscle evolution.